2018
DOI: 10.1037/dev0000574
|View full text |Cite
|
Sign up to set email alerts
|

Violent video games, externalizing behavior, and prosocial behavior: A five-year longitudinal study during adolescence.

Abstract: Decades of research on the effects of media violence have examined associations between viewing aggressive material in the media and aggression and prosocial behavior. However, the existing longitudinal studies have tended to exclusively examine aggression and prosocial behavior as outcomes, with a limited range of potential mediators. The current study examines associations between playing violent video games and externalizing and prosocial behavior over a 5-year period across adolescence. Additionally, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 105 publications
2
36
0
8
Order By: Relevance
“…The fit of this more constrained model was acceptable χ 2 (41) = 1603.71, TLI = 0.949, CFI = 0.949; RMSEA = 0.037 95% CI = [0.036; 0.039]. The correlation between the latent factors of prosocial behavior at T1 and T2 was r = 0.49 ( z = 45.32, p < 0.001), which is highly similar to the coefficient reported in earlier research for a two-year interval ( r = 0.48) (Coyne et al 2018 ). Because most studies testing construct stability use a one-year interval instead of the two-year interval covered in the present study, it seems appropriate to translate the coefficient of stability into the value that would be expected for a one-year interval, which yielded a value of r = 0.70 ( z = 90.76, p < 0.001).…”
Section: Resultssupporting
confidence: 80%
“…The fit of this more constrained model was acceptable χ 2 (41) = 1603.71, TLI = 0.949, CFI = 0.949; RMSEA = 0.037 95% CI = [0.036; 0.039]. The correlation between the latent factors of prosocial behavior at T1 and T2 was r = 0.49 ( z = 45.32, p < 0.001), which is highly similar to the coefficient reported in earlier research for a two-year interval ( r = 0.48) (Coyne et al 2018 ). Because most studies testing construct stability use a one-year interval instead of the two-year interval covered in the present study, it seems appropriate to translate the coefficient of stability into the value that would be expected for a one-year interval, which yielded a value of r = 0.70 ( z = 90.76, p < 0.001).…”
Section: Resultssupporting
confidence: 80%
“…For example, when playing alone, prosocial behavior is relatively similar across participants who play ultraviolent, violent, and nonviolent video games (Tear & Nielsen, 2014). Some study findings indicate that VVGs themselves have little to no relationship to prosocial behavior (Ferguson, 2015; Tear & Nielsen, 2013), whereas others demonstrate that VVGs are associated with lower prosocial behavior (Anderson & Bushman, 2001; Coyne, Warburton, Essig, & Stockdale, 2018). However, research has demonstrated that adding a prosocial aspect to the game, such as protecting another character—either one controlled by another player or an NPC—can increase prosocial and helping behavior (Gitter, Ewell, Guadagno, Stillman, & Baumeister, 2013; Velez, Greitemeyer, Whitaker, Ewoldsen, & Bushman, 2016; Velez et al, 2014).…”
Section: Resultsmentioning
confidence: 94%
“…In addition, adolescents who affiliate with supportive peers behave prosocially more frequently (Stotsky, Bowker, & Etkin, 2019), whereas peer rejection is associated with less frequent prosocial behavior levels (Di Giunta et al, 2018). Moreover, exposure to prosocial media is associated positively with adolescents’ prosocial behaviors, whereas exposure to violent media is negatively linked to such actions (Coyne, Warburton, Essig, & Stockdale, 2018). Finally, sympathy, perspective taking, moral reasoning, and moral values are generally positively associated with prosocial behaviors (Cassels, Chan, Chung, & Birch, 2010; Ongley & Malti, 2014).…”
Section: Who Shares With Whom In What Circumstances and For What Rementioning
confidence: 99%